Development of integrated system for reverse engineering for biomedical devices - Chua, Chee Kai. (2008)
This report describes the work done in the general area of reverse engineering for biomedical applications, prostheses via rapid prototyping and tooling techniques, and intelligent techniques in assisted surgery. Physical 3D models can be fabricated using RP technique. The combination of RP and reverse engineering has been applied several medical areas. An integrated reverse engineering system is developed to link a hospital with RP facilities in NTU. Two case studies are reported which were conducted to test the feasibility of the system, i.e., nose prosthesis using laser scanning and skull replication using CT scanning. A novel manufacturing approach for the fabrication of extraoral facial prostheses is introduced in this paper. The approach combines or integrates 3 key manufacturing technologies, namely, laser surface digitizing/scanning, computer-aided design (CAD) and manufacturing (CAM), to provide automated fabrication of spatially and anatomically accurate prostheses.